Eksplorasi Penerapan Program Literasi Pada Kurikulum Merdeka Di Kelas Rendah Sdn 08 Koto Baru Kabupaten Dharmasraya - Nanda, Dodi Widia; asmaryadi, Ahmad Ilham; Novriana, Peni (Jurnal Ilmiah Dikdaya, 2024)
This research is motivated by the low interest in literacy in the independent curriculum of low-grade students of SDN 08Koto Baru. This is shown by the lack of interest of students to prioritize literacy activities in daily life. This is caused by twofactors, namely internal factors and external factors. Internal factors are from within the students themselves, for example lowliteracy interest and lack of motivation of students, then external factors are from outside the students, such as the familyenvironment, friends, and school environment. This type of research is qualitative research with a case study approach, with theresearch instruments being the researcher himself, questionnaires, interviews, and observations. Then the data collectiontechnique uses observation techniques, interview techniques, and documentation. The results of the study revealed that theimplementation of the literacy program in the independent curriculum has been carried out with various routine activities carriedout by students. Such as reading activities 15 minutes before learning starts, mini libraries (reading corners), and library visits.However, there are several obstacles faced in the implementation of this literacy program, namely gadgets, students get boredquickly, and the lack of updating the book collection owned by the SDN 08 Koto Baru library.